Analisis Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Kinerja Karyawan: Literatur Review - Khairunisa Deri Hatasya (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The implementation of occupational safety and health programs is one of the maintenance provided by the company to the workforce. The purpose of this study was to analyze the effect of Occupational Safety and Health on employee performance. This research uses the literature review method. The results of the review show that there are 5 studies in 2019 to 2023. The research design mostly uses descriptive analysis research design with a quantitative approach. Based on the overall journal analysis, there is a relationship between the application of OHS in improving performance in workers. The conclusion of this study is that occupational safety and health can have a major effect on employee work performance. Employees will have good performance in their work when Occupational Safety and Health in a company has been running well too.